2020
DOI: 10.1039/c9ee02410g
|View full text |Cite
|
Sign up to set email alerts
|

Transforming the carbon economy: challenges and opportunities in the convergence of low-cost electricity and reductive CO2 utilization

Abstract: Renewable electricity can be leveraged to produce fuels and chemicals from CO2, offering sustainable routes to reduce the carbon intensity of our energy and products-driven economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
248
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(248 citation statements)
references
References 148 publications
0
248
0
Order By: Relevance
“…Secondly, there is energy consumption when capturing the carbon source. As a result of the high cost, different conversion approaches also need to meet the expected economic benefits, [7] as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, there is energy consumption when capturing the carbon source. As a result of the high cost, different conversion approaches also need to meet the expected economic benefits, [7] as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Many reviews and papers have discussed the costs and techno-economic feasibility of CO 2 utilization routes, a selection (not exhaustive) of which is the following: Centi and Perathoner (2010), Quadrelli et al (2011), Aresta et al (2013), Centi et al (2013), Barbato et al (2014), Centi and Perathoner (2014), Perathoner and Centi (2014), Laumb et al (2013), Ampelli et al (2015), Dimitriou et al (2015), PĂ©rez-Fortes et al (2016), Naims (2016), Navarrete et al (2017), Ordomsky et al (2017), Senftle and Carter, (2017), Zheng et al (2017), Iaquaniello et al (2018), Koytsoumpa et al (2018), GonzĂĄlez-Garay et al (2019a), Hepburn et al (2019), Jens et al (2019), , Grim et al (2020), Meunier et al (2020), Mustafa et al (2020), , and Zimmermann et al (2020). Although the conclusions are often contradictory, it is commonly suggested that there still exist large barriers for the implementation and deployment of CCU.…”
Section: Introductionmentioning
confidence: 99%
“…17 On the other hand, low temperature electrochemical CO2 conversion to multi-carbon products is relatively immature (TRL of 2-4) and often limited in labscale testing. 13,17 Interestingly, the electrochemical route offers a number of potential opportunities, including modular scaling for small to large-scale applications, lower capital investment, load balancing for electric grid, storage of intermittent renewable electricity (e.g., wind or solar energy) into energy-dense hydrocarbons that can be transported and traded globally etc. 13 With continuous reduction in renewable electricity price, electrochemical CO2 conversion technologies could become economically competitive with thermochemical and conventional fossil-based synthesis pathways 12,18 .…”
Section: Introductionmentioning
confidence: 99%
“…13,17 Interestingly, the electrochemical route offers a number of potential opportunities, including modular scaling for small to large-scale applications, lower capital investment, load balancing for electric grid, storage of intermittent renewable electricity (e.g., wind or solar energy) into energy-dense hydrocarbons that can be transported and traded globally etc. 13 With continuous reduction in renewable electricity price, electrochemical CO2 conversion technologies could become economically competitive with thermochemical and conventional fossil-based synthesis pathways 12,18 . To date, depending on the reaction conditions, operating parameters and catalyst used, over 16 different chemicals have been produced via electrochemical CO2 conversion, including carbon monoxide (CO), formic acid (HCOOH), methane (CH4), methanol (CH3OH), ethylene (C2H4), ethanol (C2H5OH), n-propanol (C3H7OH), acetic acid (CH3COOH) etc.…”
Section: Introductionmentioning
confidence: 99%